Taxes and Corporate Capital Structure in an Incomplete Market - Taggart, Robert A. (Journal of Finance, 1980)
This paper extends Merton Miller's 1977 analysis of corporate capital structure decisions to the incomplete capital markets case. As in Miller's model, aggregate demand for corporate leverage is curtailed as interest rates on taxable bonds rise. Unlike Miller's model, however, capital structure is not a matter of indifference to all equilibrium shareholders. Market incompleteness and tax arbitrage restrictions combine to prevent marginal rates of substitution from being equalized for all investors and hence their preferences are not unanimous. In addition, costs associated with debt induce a tendency for lower cost firms to issue a larger proportion of total corporate debt.